(untitled) (Journal of Pakistan Orthopaedic Association, 2016)
Objective: To assess the effectiveness of transverse acetabular ligament (TAL) as a guide for acetabular cup ante version during total hip arthroplasty and its effect on postoperative hip dislocation. Methods: This descriptive case series was on 117 patients suffering from Hip pathologies underwent elective primary total hip arthroplasties (THA). Patients were examined radiologically postoperatively to calculate abduction (Inclination) angle and ante version angle. All patients were followed up for a period of 6 months for clinical and radiological assessment. Effectiveness was assessed as rate of postoperative hip dislocation. One sample Chi-square goodness of fit test was used to assess statistical significance for proportion of patients in safe zone with p < .05 as statistical significant. Results: Out of 117 THAs, 42(35%) patients were operated for avascular necrosis of femoral head, 27(23%) for hip osteoarthritis, 22(18%) for rheumatoid arthritis of the hip and 24(20%) for fracture neck of femur. There were 75 males and 52 females with range of age from 17 to 72 years. The mean abduction angle was calculated on postoperative AP radiograph to be 42.940 range (390 -460 ) degrees. The hip anteversion angle was measured on a cross table lateral radiograph of the operated hip .The mean ante version angle of acetabular cup on a cross table lateral view of the hip was 16.880 degrees range (130 -220 ). The rate of postoperative hip dislocation was 0.85% at six months follow up. Conclusion: Transverse acetabular ligament and an excellent patient specific tool to guide us towards the correct ante version of the acetabular component and can assist to position the acetabular component in THR. Keywords: Transverse acetabular ligament, Hip arthroplasty, Hip dislocation.